Dengue NS5 modulates expression of miR‐590 to regulate ubiquitin‐specific peptidase 42 in human microglia. Issue 4 (12th March 2019) - Mishra, Ritu; Sood, Vikas; Banerjea, Akhil C.
Abstract: Dengue virus (DENV), a member of Flaviviridae family, has become neurovirulent in humans after rapid geographical expansion. Host proteasomal machinery contains both ubiquitin ligases as well as deubiquitinases (DUBs), known to influence key cellular and biological functions. MicroRNA‐mediated modulations of DUBs in case of DENV infections have not been explored yet. DENV propagation, MiRNA overexpression, miRNA knockdown, transfection, RT‐PCR, luciferase assay, and western blotting have been used in this study to establish the interaction of miR‐590 and USP42. DENV infection in human microglial cells resulted in downregulation of host DUB‐USP42 in a dose‐dependent manner and DENV‐NS5 gene alone was found to be sufficient for this downregulation. miR‐590 was upregulated upon NS5 overexpression in a dose‐dependent manner. Downregulation of USP42 was observed with miR‐590 overexpression. The specificity of this regulation was confirmed by miR‐590 mimic and anti‐miR transfections in microglial cells. miR‐590 overexpression and knockdown affected the expression level of TRAF6 in indirect manner in microglial cells. The luciferase assay demonstrated the direct regulatory interaction between miR‐590 and 3'UTR of USP42. These findings establish that DENV‐NS5 protein can potentially modulate the host deubiquitinase protein USP42 expression via altering cellular miR‐590 levels in human microglial cells.